SENYAWA ALAMI DAUN BAWANG UNTUK DIABETES: PENDEKATAN IN SILICO TERHADAP PPAR-γ - Hidayah, Himyatul; Ruswanto; Mindawati , Erisa; Amal, Surya; Farhamzah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Leek leaves (Allium fistulosum L.) are plants that contain flavonoid compounds with diverse biological activity potential. This study aims to examine the stable interaction of the docking results between the PPAR-γ receptor complex structure and the best candidate flavonoid compounds in leek leaves as antidiabetic candidates. The method used in this study is quantitative and designed using molecular docking techniques based on computational molecular dynamics (MD), which simulates the dynamic behaviour of a molecular system as a function of time, treating each entity in the simulation box (protein, ligand, or water, if present) as flexible. The results of molecular docking on 16 onion leaf flavonoid compounds showed that hesperidin had the smallest Gibbs free energy (ΔG) of -10.0 kcal/mol, which is close to that of natural ligands. The RMSD and RMSF values are sufficiently stable. Hesperidin also has good pharmacokinetic properties and is non-toxic, thus meeting the criteria for drug-likeness as a potential oral drug candidate. These findings indicate the potential for developing flavonoid compounds, particularly hesperidin from onion leaves, as a candidate for an antidiabetic drug by inhibiting the PPARγ receptor. This study provides a foundation for further in vitro and in vivo studies to validate its biological activity.